ITGAL as a Prognostic Biomarker Correlated With Immune Infiltrates in Gastric Cancer - Zhang, Junchang; Wang, Han; Yuan, Cheng; Wu, Jing; Xu, Jiannan; Chen, Songyao; Zhang, Changhua; He, Yulong (Frontiers in Cell and Developmental Biology, 2022)
Integrin Alpha L (ITGAL), one member of the integrins family, which the abnormal expression is linked with carcinogenesis and immune regulation. However, the relation between ITGAL and the prognosis of gastric cancer (GC) and tumor-infiltrating lymphocytes (TILs) are not well understood. The differential expressions of ITGAL in human tumors and the clinical prognosis in GC were systematically analyzed via multiple databases including Gene Expression Profiling Interaction Analysis (GEPIA), UALCAN, Tumor Immune Estimation Resource (TIMER) and Kaplan-Meier (KM) plotter. TIMER, GEPIA and TISIDB databases were performed to comprehensively investigate the correlation between ITGAL and tumor infiltration immune cells. Also, further results were investigated by immunohistochemistry, qRT-PCR and western blot. We found that ITGAL expression in GC samples was considerably increased than in peritumor samples. Sample type, subgroup, cancer stage, lymphatic node stage and worse survival were strongly related to high ITGAL expression. Moreover, upregulated ITGAL expression was strongly connection with immunomodulators, chemokines and infiltrating levels of CD8+, CD4+ T cell, B cell, monocyte, neutrophil, macrophage, T cell regulatory, NK cell and myeloid dendritic cell in stomach adenocarcinoma (STAD). Specifically, Immunohistochemistry and bioinformatic analysis showed that ITGAL expression was shown to have strong relationships with various immunological marker sets including PD1 (T cell exhaustion marker). In conclusion, ITGAL is a prognositic biomarker for GC patients, it might regulate tumor immune microenvironment to lead poor prognosis. Further studies are essential to explore therapeutic targeting ITGAL.